The Existence of Maudu’i's Interpretation Method: A Study of Historical Background, Urgency, and Relevance in the Modern Century - Panjaitan, Meidita Aulia; Azahra, Khalida Zia Fitrah (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2026)
The tafsir maudu’i (thematic interpretation) represents a significant innovation in modern Qur’anic exegesis, emphasizing a thematic and comprehensive understanding of the Qur’an’s content. This study aims to examine the historical factors underlying the emergence of the tafsir maudu’i method, explain its urgency amid increasingly complex humanitarian issues, describe the scholars who played a key role in its development, analyze the fundamental differences between tafsir maudu’i and tafsir muqaran, and identify the reasons why tafsir maudu’i has gained prominence in the modern era. This research employs a qualitative-descriptive approach through a literature-based analysis of both classical and contemporary sources. The findings indicate that tafsir maudu’i holds significant urgency in addressing complex social, theological, and humanitarian issues in the modern context. Its importance lies in its ability to integrate various verses related to a single theme, thereby providing a holistic and contextual understanding. In the modern context, tafsir maudu’i serves as an epistemological approach that emphasizes the relationship between the revealed text and social reality. Thus, the existence of tafsir maudu’i functions not only as a method of interpretation but also as a hermeneutical paradigm that bridges divine values and contemporary challenges.